PRACTICAL FEATURES OF THE USE OF DEBATES AND GAMING TECHNOLOGY IN THE CLASSROOM - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2022)
This article covers these features that pupil, being based on the skills generated with the help of a debatable method, it is capable to apply and develop these skills in concrete situations of dialogue, carrying out socially significant roles and skill to assert the position in problem situations. In this article have been analyzed all these methods and the receptions raising quality of training to foreign language on the basis of studying of various techniques of teaching, used in work with children. Many of receptions can be applied with success at teaching children of younger and more advanced age.